Neonatal resuscitation guidelines - A survey among pediatricians attending a newborn conference in North Kerala - Pavithran, Kavitha; Jacob, Ambili Susan; Diwakaran, Binoo (Indian Journal of Child Health, 2017)
Background: Meticulous understanding and adequate skills for prompt neonatal resuscitation by health-care personnel working in the labor, maternity, and newborn units is important. Various studies have identified areas of non-uniformity among pediatricians regarding neonatal resuscitation practices. Aim: The aim is to evaluate the knowledge among pediatricians regarding the current neonatal resuscitation guidelines and the practices they follow in their unit. Materials and Methods: A cross-sectional survey of 17 questions, based on guidelines of Neonatal Resuscitation Program (NRP) 2015 and Navjaat Shishu Suraksha Karyakram, was conducted using a questionnaire distributed to pediatricians attending a neonatology conference. The responses were noted and analyzed using SPSS. The relation of knowledge score with demographic profile and status of training was assessed. Results: The response rate was 66%. Majority (52%) of the participants were working in private hospitals. Neonatal intensive care unit with mechanical ventilation facilities was available for 60% of respondents. Nearly 40% were trained in neonatal resuscitation. About 85% reported correct knowledge regarding effective chest compressions. Nearly 50% reported the use of room air for bag and mask ventilation during resuscitation in babies more than or equal to 35 weeks. Tracheal suction was practiced by 54% in meconiumstained liquor, and 55% practiced delayed cord clamping for 30-60 s. Nearly 62% did not have oxygen blender in the resuscitation corner, whereas 33% had cardiac monitor. No significant association was found between the place of work and knowledge score (using Chi-square test for association, p=0.280). Designation of the delegate did not have a significant association with knowledge score (p=0.300). Knowledge score of delegates from teaching hospitals was not superior to those from the non-teaching hospitals. No significant association was found between knowledge score and training (p=0.999). Conclusions: Knowledge about neonatal resuscitative practices in pediatricians as well as infrastructural facilities needs to be improved with regular NRP training.